2009
DOI: 10.1097/sle.0b013e31819ca96b
|View full text |Cite
|
Sign up to set email alerts
|

Postlaparoscopic Iatrogenic Pseudoaneurysms of the Arteries of the Peritoneal and Retroperitoneal Space

Abstract: A total of 66 cases were retrieved. Postlaparoscopic iatrogenic pseudoaneurysms are late manifestations of arterial complications developing during routine laparoscopy. There are 66 reported cases of this type of complication in the literature. The majority occurs in the arteries of the operation field of the respective laparoscopic procedure. Distal vessels are involved less frequently. They usually present after a mean period of approximately 6 weeks. The hepatic and renal arteries are usually affected. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 44 publications
0
10
0
1
Order By: Relevance
“…We found 97 eligible studies and a sum of 134 patients who presented with at least one symptomatic PA following LC during a 26-year period (1994–2020). [ 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 63 64 65 66 67 68 69 70 71 72 73 74 75 76 77 78 79 80 81 82 83 84 85 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We found 97 eligible studies and a sum of 134 patients who presented with at least one symptomatic PA following LC during a 26-year period (1994–2020). [ 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 63 64 65 66 67 68 69 70 71 72 73 74 75 76 77 78 79 80 81 82 83 84 85 …”
Section: Resultsmentioning
confidence: 99%
“…Two previous reviews of the literature have been published in the past which provided valuable information on this subject. [ 6 7 ]…”
Section: Introductionmentioning
confidence: 99%
“…In 73 patients out of 193, the vascular injury occurred in the cystic artery, which was the most affected vessel [ 6 ]. Parthenis et al in a review of literature mentioned the rarity of vascular pseudoaneurysms after laparoscopic surgeries and identified 66 relative cases where only three referred to cystic artery pseudoaneurysm and most of them concerned the right hepatic artery [ 7 ]. Another more recent review by Lampropoulos et al confirmed that the right hepatic artery was the most common site of pseudoaneurysm development, followed by the cystic artery [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…Another more recent review by Lampropoulos et al confirmed that the right hepatic artery was the most common site of pseudoaneurysm development, followed by the cystic artery [ 8 ]. Among laparoscopic procedures, laparoscopic cholecystectomy is associated more often with the formation of pseudoaneurysm followed by laparoscopic nephrectomies [ 7 ]. Clinical presentation of CAP may be in the early or late postoperative period, although in most cases, may occur in the first postoperative month [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…In laparoscopic surgeries, iatrogenic pseudoaneurysms have been reported as the causes of late postoperative bleeding, with a mean time of 6 weeks between the surgery and discovery of the pseudoaneurysm. 2 Similarly, in patients undergoing prostatectomies and cystectomies, pseudoaneurysms were the reported causes of delayed postoperative bleeding. 3 Among patients with cervical cancer, a case of life-threatening massive bleeding caused by a ruptured pseudoaneurysm was reported.…”
Section: Discussion and Literature Reviewmentioning
confidence: 99%